KAPLAN’S LESION: A CASE REPORT ON THE COMPLEX DISLOCATION OF THE INDEX FINGER IN A WEIGHTLIFTER - Arora, Yuvraj; Mohapatra, Ashutosh; Choudhury, Priyam; Jangir, Rajat (Journal of Ayub Medical College Abbottabad, 2022)
Background: Complex Dislocation of the metacarpophalangeal joint of the hand is a rare and unusual injury. These are also called as Kaplan’s Lesion. They are divided into complex/irreducible and simple/reducible dislocation. Two approaches exist regarding their surgical intervention. We present a case of a 36-year-old weightlifter who presented to us with this uncommon entity and who was successfully treated with a dorsal approach. This case is presented to highlight the occurrence of this dislocation along with a brief discussion on its etiopathogenesis and management.